Is hard physical work in the early working life associated with back pain later in life? A cross-sectional study among 5700 older workers - Lars L Andersen; Rúni Bláfoss; Sebastian Venge Skovlund; Rubén López‐Bueno; Joaquin Calatayud; Emil Sundstrup (BMJ Open, 2020)
Objectives Physically demanding work increases the risk of developing musculoskeletal disorders during working life, with low back pain (LBP) as the most prevalent and debilitating musculoskeletal disorder worldwide. However, a lack of knowledge exists about the role of early working years on musculoskeletal health later in life. This study investigated whether an exposure–response association exists between physical demands in early working life and risk of LBP in later working life.Design Cross-sectional study.Setting, participants and outcome measure In the SeniorWorkingLife study, 5909 wage earners aged ≥50 years with currently sedentary work replied to a questionnaire survey in 2018 about physical work demands during their first working years (exposure) and current LBP (outcome). Associations between physical work demands in the early working years and current LBP were modelled using general linear models controlling for various confounders, combined with model-assisted weights based on national registers.Results Hard physical work during early working life was associated with more intense LBP later in life among senior workers with currently sedentary jobs. In the fully adjusted model, workers with ‘standing/walking work with lifting/carrying’ and ‘heavy or fast work that is physically strenuous’ during the first years of working life reported higher LBP intensity than those with sedentary work during their first working years (0.2 (95% CI, 0.0 to 0.4) and 0.6 (95% CI, 0.4 to 0.9), respectively).Conclusion Work involving lifting/carrying or work that is physically strenuous in early life is associated with higher intensity of LBP among older workers with currently sedentary employment. These findings suggest that early working life may have an impact on later working years and underscore the necessity for careful introduction and instruction to the working environment for retaining musculoskeletal health and prolonging working life.Trial registration number NCT03634410.